Thermal performance of resource-efficient geopolymeric mortars containing phase change materials - Kheradmand, M. (2018)
Energy efficiency is not only the most cost effective way to reduce emissions but also a way to improve competitiveness and create employment. This paper reports experimental results on the thermal performance of geopolymeric mortars containing different percentages of phase-change materials-PCMs. These materials have a twofold positive impact concerning eco-efficiency. On one hand, the mortars are based on industrial waste contributing for resource efficiency. And on the other hand, PCM based mortars have the capacity to enhance the thermal performance of the buildings. Five groups of alkali-activated based mortars with different PCM percentages were produced and placed on a panel within a small-scale prototype for thermal performance testing. The results show that the thermal conductivity of the mortars decreased with the increase in the percentage of the PCM. The results also show that the thermal performance of the PCM based mortars allowed for a stronger attenuation of the temperature amplitudes. Both for heating and cooling loads.